miR-223 and other miRNA's evaluation in chronic kidney disease: Innovative biomarkers and therapeutic tools - Valérie Metzinger-Le Meuth; Laurent Metzinger (Non-coding RNA Research, 2019)
microRNAs (miRNAs) represent a recent breakthrough regarding gene expression regulation. They are instrumental players known to regulate post-transcriptional expression. miRNAs are short single stranded RNAs that base-pair with target mRNAs in specific regions mainly within their 3′ untranslated region. We know now that miRNAs are involved in kidney physiopathology. We outline in this review the recent discoveries made on the roles of miRNAs in cellular and animal models of kidney disease but also in patients suffering from chronic kidney disease, acute kidney injury and so forth. miRNAs are potential innovative biomarkers in nephrology, but before being used in daily clinical routine, their expression in large cohorts will have to be assessed, and an effort will have to be made to standardize measurement methods and to select the most suitable tissues and biofluids. In addition to a putative role as biomarkers, up- or down-regulating miRNAs is a novel therapeutic approach to cure kidney disorders. We discuss in this review recent methods that could be used to deliver miRNAs in a specific and suitable way in kidney and other organs damaged by kidney failure such as the cardiovascular system.